The renaissance of barrier contraception (based on the data from an international clinical trial) - Vera N. Prilepskaya; Elena A. Mezhevitinova; Elena G. Nazarenko; Elena A. Gorodnova (IP Berlin A.V., 2021)
Background. In recent years, interest in the use of barrier methods of contraception has increased, since many women prefer them in connection with the change in the epidemiological situation associated with COVID-19, with contraindications to other methods of contraception, as well as with irregular sex life and casual sexual intercourse. In addition, these methods of contraception are preferred for breastfeeding mothers and pre- and postmenopausal women. Studies of the efficacy of spermicidal agents in late reproductive age women have not previously been carried out, although their use in this population is of particular interest, since these agents do not have a systemic effect and, if used correctly, can prevent unwanted pregnancies. The article presents data from an international French-Russian study of the efficacy of spermicides containing benzalkonium chloride in late reproductive age women (over 40 years). The study was carried out on the basis of 7 private offices of obstetricians and gynecologists in France and 6 obstetric and gynecological clinics in Russia. Aim. Assessment of the contraceptive efficacy, safety and acceptability of a cream containing benzalkonium chloride in women over 40 years of age. Materials and methods. The study included non-pregnant women aged 40 and over who had at least 1 menstrual period in the past 3 months and who would like to use spermicides as contraception for at least 6 months. After a 6-month period of mandatory use of spermicide, patients could, if desired, continue to use it for the next 6 months. All women were given Pharmatex (1.2%), a vaginal cream containing benzalkonium chloride (1.2 g per 100 g of cream) as the active ingredient, 1 standard dose before each intercourse. The primary endpoint was the Pearl Index. The acceptability of the method after each use of the cream, the moisturizing effect, and the woman's and researcher's overall satisfaction with this method of contraception were also assessed. Safety was assessed using adverse event monitoring. Results. An analysis of efficacy of the study drug showed that during study, pregnancy did not occur in any of the women. Pearl Index for 12 months was 0. Over the mandatory 6-month period, the use of Pharmatex cream was assessed by patients as acceptable (to some extent acceptable, acceptable, completely acceptable) in 98% of sexual intercourse, and over the 12-month period in 98.6% of intercourse. The moisturizing effect of the cream was noted by 96.1% of women. In 6 months of the use of Pharmatex cream, overall satisfaction was rated as quite good, good, or very good by 99.3% of patients and in 12 months by 100% of patients. Adverse events were noted only in 0.5% of cases. Most of these events were assessed as unrelated to the study drug. Conclusion. The use of a benzalkonium chloride spermicidal cream can be considered an effective and acceptable method of contraception for women over the age of 40. It is well tolerated, has a moisturizing effect on the vaginal mucosa, and meets the needs and lifestyle of women. The contraceptive with benzalkonium chloride has a favorable safety profile: it does not adversely affect the normal flora of the vagina, can be used during breastfeeding, since it does not penetrate into the vascular bed and doesnt have systemic effects.